2020
DOI: 10.21203/rs.3.rs-25047/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intracytoplasmic expression of IL-6 and IL-17A in circulating CD4+ T cells are strongly associated with and predict disease activity in rheumatoid arthritis: A case-control study in Ghana

Abstract: Background T cell cytokines play important roles in the development and progression of rheumatoid arthritis (RA). Loss of Th1/Th2 and Th17/Treg balance has been reported in several inflammatory autoimmune diseases. However, their role in RA within the Ghanaian context has not been explored. Here, we evaluated the intracytoplasmic CD4 + T cell cytokine patterns in rheumatoid arthritis patients in Ghana and determined their relationship with disease activity. Methods This case-control study included 48 newly-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, Th1, Th2, Th17, and Treg cells, as four important subtypes of CD4 + T cells, are closely associated with the occurrence and development of RA. 37,38 Studies have found that Th1 and Th17 cells play an important role in the development of RA, while Th2 and Treg cells may play a protective role in RA patients. 39 Therefore, RA patients often have an imbalance in the number of Th1, Th2, Th17, and Treg cells.…”
Section: Menthone Restricts the Transcriptional Expression Of T Cell ...mentioning
confidence: 99%
“…However, Th1, Th2, Th17, and Treg cells, as four important subtypes of CD4 + T cells, are closely associated with the occurrence and development of RA. 37,38 Studies have found that Th1 and Th17 cells play an important role in the development of RA, while Th2 and Treg cells may play a protective role in RA patients. 39 Therefore, RA patients often have an imbalance in the number of Th1, Th2, Th17, and Treg cells.…”
Section: Menthone Restricts the Transcriptional Expression Of T Cell ...mentioning
confidence: 99%